Kesalahan Berbahasa Arab Mahasiswa Tataran Sintaksis dalam Penulisan Insya’ - Sarif, Suharia (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
Identifying Arabic errors among students is important for teaching staff, to determine the right lag in choosing the next learning strategy. The purpose of the study was to analyze the forms of Arabic errors at the syntactic level in writing insya' students in Arabic Language Education at IAIN Sultan Amai Gorontalo. This research is descriptive research with a type of qualitative research, which is to obtain an overview of syntactic errors on worksheets insya' by students. The results of the analysis found errors at the syntactic level which include: 1) errors in the use of the number of ismiyah, 2) errors in the number of fi'liyah, 3) errors in the use of na’tu and man’u>t, 4) errors in the arrangement of at}fu and ma’t}u>f ilaih.